Time-differentiated supply at customer sites: Analysing the service costs - Mohsin Nasir Jat (Logistics Research, 2017)
Common in IT equipment support and emergency service operations, time-based service differentiation involves setting different service time windows to respond to different classes of service calls. These time windows can be associated with providing service parts (materials) at customer sites. It is reasonable to expect that the impact of different service time options on service costs is realized for strategic and operational planning. However, the question of how different service time limits impact on service costs has largely been overlooked in the existing literature. The paper focuses on this question and presents an estimate cost model based on a stylized system considering hierarchical and non-hierarchical organizations of service facilities. The impact of varying service time limits and the demand fractions for different service times on inventory, transportation and distribution network setup costs is investigated. The findings show that when service time requirements become stricter, requiring more decentralized distribution, the inventory levels do not increase in all cases, while travelling to reach customers reduces proportionally. The analysis highlights that a non-hierarchical setup of facilities, treating different service time requests in a uniform fashion, can perform better in certain cases.
Keywords: 650; Distribution; Inventory; Transportation; Decentralization; Time constrained services